Research on the Construction of Age-Friendly Community Based on Fuzzy Comprehensive Evaluation Model: Evidence from Community in Hefei of China - Pan L; Sun J; Zhou R (Dove Medical Press, 2021)
Lin Pan,1,2 Jian Sun,3 Rongting Zhou2 1Department of Basic Education, Party School of Anhui Provincial Committee (Anhui Academy of Governance), Hefei, 230022, People's Republic of China; 2Department of Sci-Tech Communication and Policy, University of Science and Technology of China, Hefei, 230026, People's Republic of China; 3School of International and Public Affairs, Shanghai Jiao Tong University, Shanghai, 200030, People's Republic of ChinaCorrespondence: Jian SunSchool of International and Public Affairs, Shanghai Jiao Tong University, 1954 Huashan Road, Xuhui District, Shanghai, 200030, People's Republic of ChinaTel +86-188-1693-0536Email sjjjw6@sjtu.edu.cnBackground and Aim: The construction of an age-friendly community is beneficial to meeting the needs of the elderly and coping with ageing. It is significant to evaluate the quality of age-friendly communities through scientific methods. The study aims to evaluate the livability of communities among the elderly in China.Methods: The data used in this study were sourced from the community of Hefei in China, including 1426 participants aged 60 and above. Taking community in Hefei of China as an example, the analytic hierarchy process fuzzy comprehensive evaluation model was used to evaluate the community. Furthermore, this paper constructs an evaluation index system for the livable elderly community and evaluates the comprehensive community system with the fuzzy comprehensive evaluation method.Results: This study constructs the evaluation index system of an age-friendly community that includes five first-level evaluation indexes and 33 second-level evaluation indexes. The first-level indexe satisfaction from high to low are community safety, community comfort, community health and convenience, and community service. Among them, flat roads (more than 74.3%), greening (more than 78%), quietness (more than 76.8%), health situation (more than 65%), and public transport facilities (more than 66%) were relatively satisfactory. However, in terms of community service, the overall satisfaction of the elderly is not high.Conclusion: This study revealed that the level of the age-friendly community in Hefei of China is relatively high. The community safety score is the highest, comfort is relatively high, followed by community health and convenience. The score of community service was low. Moreover, the results indicated that improving the quality of service has become the key to improving the satisfaction of the elderly in the community.Keywords: age-friendly community, satisfaction, index system, fuzzy comprehensive evaluation method, China